IMPLEMENTATION OF TWO-FACTOR AUTHENTICATION ACCESS CONTROL IN WEB-BASED SERVICES WITH CLOUD COMPUTING USING C#.NET - R, Gokila; A, Mannimaran (Innovare Journal of Engineering and Technology, 2018)
In this project, our propose preventing private information leakage at the phase of access authentication. I introduces two access control mechanism here: (1) user secret key and (2) security device. Our proposed mainly consists of two entities; they are attribute-issuing authority and trustee. Attribute-issuing authority is responsible to generate user secret key for each user. Trustee is responsible for initializing the security device. Secret key cannot use by user in another device. Security device content store inside the security device is not accessible nor modifiable once it is initialize. User can access the system means and both mechanisms are need. Detailed security analysis shows that the proposed two-factor authentication access control system achieves the desired security requirements.